2019
DOI: 10.1515/cclm-2019-0699
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site performance evaluation and Sigma metrics of 20 assays on the Atellica chemistry and immunoassay analyzers

Abstract: Background The Atellica Solution comprises chemistry (CH) and immunoassay (IM) analyzers. Recently, six early adopter clinical laboratories across Europe evaluated the analytical performance of 20 CH and IM assays. To measure analytical performance quality, Sigma metrics were calculated for individual-site and pooled-site results. Methods Precision, detection capability, linearity, and method comparison studies were performed according to Clinical Laboratory Standards Institute protocols. Global Sigma metrics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…(1) lack of consistency in performing the operating procedures by personnel among different laboratories; (2) reagent lot numbers that were not exactly the same; and (3) the potential impact of differences in temperature and humidity conditions among the laboratories on the detection system. Fasano et al 30 conducted a multicenter study based on the Atellica chemistry/immunoassay analyzer using sigma metrics to evaluate the analytical performance of 20 assays.…”
Section: Discussionmentioning
confidence: 99%
“…(1) lack of consistency in performing the operating procedures by personnel among different laboratories; (2) reagent lot numbers that were not exactly the same; and (3) the potential impact of differences in temperature and humidity conditions among the laboratories on the detection system. Fasano et al 30 conducted a multicenter study based on the Atellica chemistry/immunoassay analyzer using sigma metrics to evaluate the analytical performance of 20 assays.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the EQA surveys, reducing of multiple bias values to single value has been encountered in multicenter studies on Sigma metrics in clinical laboratory. Two recent studies have estimated the pooled bias from individual site bias values obtained from method comparison studies for Sigma calculation ( 2 , 3 ). They have reported the pooled bias values with minus sign for some assays.…”
Section: To the Editormentioning
confidence: 99%
“…A recent performance evaluation of Atellica CH 930 chemistry analyzer was performed at 4 different laboratories across Europe for 13 chemistry analytes [14]. In this study, Atellica CH 930 was compared with the ADVIA XPT systems (one site) and with the ADVIA 1800 systems (three sites) [14].…”
Section: Sigma Metrics For Assessment Of Laboratory Analytical Performancementioning
confidence: 99%
“…A recent performance evaluation of Atellica CH 930 chemistry analyzer was performed at 4 different laboratories across Europe for 13 chemistry analytes [14]. In this study, Atellica CH 930 was compared with the ADVIA XPT systems (one site) and with the ADVIA 1800 systems (three sites) [14]. This robust multicentric study reported that, at the individual-site level, 90% of chemistry assays performed at 4 Sigma or higher (CLIA-TE a was used) and 100% performed at 3 Sigma or higher, thus concluding in favor of the new Atellica CH 930 analyzer and its use in the clinical laboratory [14].…”
Section: Sigma Metrics For Assessment Of Laboratory Analytical Performancementioning
confidence: 99%
See 1 more Smart Citation